Bionanofluid flow through a moving surface adapting convective boundary condition: sensitivity analysis - Sze, Qi Chan; Aman, Fazlina; Mansur, Syahira (Penerbit Akademia Baru, 2019)
The paper discusses a sensitivity analysis on a water-based bionanofluid having nanoparticles and living microorganisms flows over a moving surface. Mathematical model is constructed on the basis of Buongiorno model and a thermal convective boundary condition is taken over to replace the conventional fixed surface temperature. Numerical shooting technique is to follow closely behind the similarity transformation to solve the system of governing equations. The output parameters of interest are believed to be contingent on the governing input parameters. Obviously, the skin friction coefficient as well as the surface shear stress will only affected by the velocity ratio parameter; while the inclusion of thermal convective boundary conditions influenced the temperature profile, confined movement of the nanoparticles and living microorganisms. Focus on the response of local density of motile microorganisms to the variation of input parameters, an experimental scheme integrated with sensitivity analysis is designed. As highlighted, the local density of motile microorganisms is more sensitive to the bioconvection Péclet number rather than other governing parameters. The findings believed to offer preliminary guideline for further lab-based experiments.